2008
DOI: 10.1124/mol.107.044115
|View full text |Cite
|
Sign up to set email alerts
|

The NR1 M3 Domain Mediates Allosteric Coupling in theN-Methyl-D-aspartate Receptor

Abstract: N-Methyl-D-aspartate (NMDA) receptors play a critical role in both development of the central nervous system and adult neuroplasticity. However, although the NMDA receptor presents a valuable therapeutic target, the relationship between its structure and functional properties has yet to be fully elucidated. To further explore the mechanism of receptor activation, we characterized two gain-of-function mutations within the NR1 M3 segment, a transmembrane domain proposed to couple ligand binding and channel openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…An increase in LBD cleft closure upon channel opening (Fig. 6 B) is supported by direct evidence from Blanke and VanDongen (47). These authors found that mutations at a conserved position (referred to as A7) near the N-terminus of the GluN1 M3 helix increased the preference of the channel for the open state, and at the same time also decreased the accessibility to the LBD cleft.…”
Section: Discussionsupporting
confidence: 66%
“…An increase in LBD cleft closure upon channel opening (Fig. 6 B) is supported by direct evidence from Blanke and VanDongen (47). These authors found that mutations at a conserved position (referred to as A7) near the N-terminus of the GluN1 M3 helix increased the preference of the channel for the open state, and at the same time also decreased the accessibility to the LBD cleft.…”
Section: Discussionsupporting
confidence: 66%
“…6E). We do not fully understand this difference between the subunits but it may be a manifestation of subunit-specific contributions to channel gating (e.g., (Banke and Traynelis, 2003; Blanke and VanDongen, 2008). Nevertheless, the key point here is that the strong correlation within a subunit strongly supports the idea that potentiation is being driven mainly by an increase in P o .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the functional significance of the different conformers and how they might arise and be constrained during biosynthesis is unknown. In terms of functional properties, subunit-specific differences in the LBD-TMD linker structure may underlie subunit-specific contributions to ion permeation (Watanabe et al, 2002) and channel gating (Banke and Traynelis, 2003, Sobolevsky et al, 2007, Blanke and VanDongen, 2008a, b) (Kussius and Popescu, 2009). Recent work from our laboratory suggests that despite subunit-specific differences in the structure of the LBD-TMD linkers, NMDA receptors undergo concerted gating that appears tightly coupled at the level of these linkers (Talukder & Wollmuth, 2011, Journal of General Physiology, in press).…”
Section: Discussionmentioning
confidence: 99%